Cytotoxicity of Chromanone Acid from the Steam Bark of Calophyllum incrassatum against P-388 Leukemia Murine Cells - Hasanah, Ulfatun; Andawiyah, Robi’atul; Taqiyah, Barrotut; Saputri, Ratih Dewi; Tjahtjandarie, Tjitjik Srie (Chimica et Natura Acta, 2025)
Calophyllum incrassatum is one of the plant species of the Calophylloceae family and is found endemic in Kalimantan and Sumatra. This study aims to isolate chromanone acid compounds from the stem bark of C. incrassatum and determine the relationship between structure and activity against murine Leukemia P-388 cells. The extraction method used was maceration using methanol solvent, partitioned with n-hexane and ethyl acetate solvents. Separation and purification of n-hexane and ethyl acetate extracts by vacuum liquid chromatography, pressed column, and radial. Two chromanone acids derivatives, isoapetalic acid (1), and methyl isoapetalic (2), have been successfully isolated from the stem bark of Calophyllum incrassatum. The structures of the two compounds were identified and elucidated using spectroscopic techniques such as UV, IR, and 1D and 2D NMR. The cytotoxic activity against murine leukemia P-388 cells of compounds 1-2 showed IC50 values of 8.51 and 1.47 µg/mL, respectively, and compound (2) exhibited high cytotoxic activity